Preventing NEETs during the Great Recession: the effects of a mandatory activation program for young welfare recipients - Cammeraat, Emile; Jongen, Egbert L. W.; Koning, Pierre (Bonn, 2017)
"We study the impact of a mandatory activation program for young welfare recipients in the Netherlands. Introduced at the end of 2009, the goal of the program was to prevent so-called NEETs (individuals not in employment, education or training). We use a large administrative data set for the period 1999-2012 and employ differences-in-differences and regression discontinuity to estimate the effects of the reform. We find that the reform reduced the number of NEETs on welfare, increased the number of NEETs not on welfare, and had no effect on the overall number of NEETs. Our finding that the reform did not reduce the total number of NEETs contrasts with previous studies, which may be due to the fact that the reform took place during a severe economic recession."